Type of Exercise Affected to Testosterone Level on Female Athletes: A Systematic Review - Prasana, I GEJ; Negara, Anak AGAP (Journal of Medicine and Health, 2025)
Testosterone is a hormone that plays an important role in stimulating muscle development and regulating fat metabolism.While exercise influences testosterone levels, females generally experience smaller increases in testosterone levels after exercise than males. This has led some female athletes to misuse testosterone, posing potential health risks and altering physiological functions. This systematic review aims to examine the effects of different exercise modalities on testosterone levels in female athletes, providing insights into optimal training approaches. A comprehensive literature search was conducted using PubMed, Google Scholar, Medline, and PEDro, with keywords including "Endurance Exercise," "Resistance Exercise," and "Testosterone Levels in Female Athletes”. Of the 45 studies screened, six met the inclusion criteria. The findings suggest that endurance exercises are associated with reduced testosterone levels, whereas resistance training, such as weightlifting and bench pressing, is linked to increased testosterone production. High-intensity resistance training may lower estrogen while elevating testosterone, enhancing muscle strength and lean body mass in female athletes. However, excessive testosterone levels may disrupt menstrual function, despite its beneficial effects on bone health. These findings suggest that resistance training can elevate testosterone levels in female athletes, whereas endurance training tends to decrease them.